ANALISIS USABILITY TESTING PADA APLIKASI SISNAKER DI BLK KABUPATEN BURU - Khoirun Nisa (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Sisnaker is an official online-based platform for the Ministry of Manpower of the Republic of Indonesia that can assist in accessing employment services and information. There are several Employment services that you can access in the SISNAKER application including Training Services, Career Hub and Help Centers. This research was conducted to measure user satisfaction in using the Sisnaker application at the Buru District Vocational Training Center using the usability testing method based on five variables, namely learnability, efficiency, memorability, errors, and satisfaction. Therefore an evaluation is needed to analyze the level of usability in an application so that it can assist in developing and improving an application so that it can identify problems faced by users. In testing the several usability aspects above, it can be concluded that the usability value of the Sisnaker application is quite good, and the aspects regarding learnability, efficiency, memorability, error, and satisfaction are already in quite good criteria. It's just that a number of things were found that needed to be repaired again, namely regarding the error rate in the application, where when logging in an error often occurs every time you enter the registered email and password. But overall the Sisnaker application is quite good.